Peran Kepemimpinan Transformasional dalam Meningkatkan Kinerja Karyawan: Kajian literatur - Adinda Zahra Septiany Rusdiono; Fadillah Nurul Fitriani; Hendra Rizki Taruna; Netty Merdiaty (Jurnal Manajemen Riset Inovasi, 2025)
In An Organization, Employee Performance Is An Important Factor That Will Affect The Success Of The Organization. The Success Of The Organization Can Be Determined By How Effective And Productive Employees Are In Achieving Maximum Results. Therefore, Employees Are Often Required To Have And Master Abilities And Skills Where This Aims To Produce Satisfactory Performance, In Addition, Employees Who Have High Motivation Tend To Be Disciplined So That From High Motivation And Discipline Employees Can Complete Tasks Well So That The Results Obtained Will Be Maximized. In Assessing Employee Performance, An Employee Performance Evaluation Is Needed Which Aims To Measure How Far Employees Maximize Their Abilities And How Much Contribution Has Been Made, Where Employees Who Have Maximum Performance Tend To Do More Productive Things, Express Innovative Thoughts, And Prioritize Increasing Customer Satisfaction, And Increasing Organizational Profits.